Comorbidities of patients with chronic obstructive pulmonary disease (COPD): thyroid abnormalities in stable COPD - Buklioska Ilievska, Daniela; Mickovski, Ivana (VM Media SP. zo.o VM Group SK, 2021)
Objective: The aim of the study is to evaluate the prevalence of thyroid abnormalities in patients with stable chronic obstructive pulmonary disease (COPD) and the relationship between thyroid disorder and ventilatory function tests and arterial blood gas analyses. Material and methods: This cross-sectional study was conducted with 60 patients with stable COPD without diagnosed thyroid disorder before the study (37 males and 23 females aged 40-75) as the Investigated Group (IG) and 30 subjects from the general population without COPD as the Control Group (CG). They were matched by age, gender and body mass index with the IG. All patients underwent laboratory tests, thyroid hormones-free thyroxin (fT4), thyroid-stimulating hormone (TSH), and free triiodothyronine (fT3), pulmonary function tests (FEV 1 , FVC%, FEV 1 /FVC, FEF25-75%), and ABG parameters (PH, PaCO 2 , PaO 2 , HCO 3 , O 2 saturation). The severity level in patients with COPD was determined according to GOLD (Global Initiative for Chronic Obstructive Lung Disease) criteria and classified into four stages GOLD I, II, III, and IV. Results: Our results presented a statistically significant difference between prevalence of thyroid hormones abnormalities in stable COPD compared to controls 18 (30.0%) vs 3 (10.0%), p = 0.0355; p < 0.05). Thyroid dysfunction among COPD patients was more common in females than males. Serum level of TSH was lower than the normal range in 18 patients (30.0%) from the IG and in 3 (10.0%) from the CG, with a statistically significant difference, p = 0.0355; p < 0.05. Thyrotoxicosis with low serum TSH and a higher serum level of fT3, according to the referent range, was present in 8 patients (13.3%), and in no patients from the CG 0 (0.0%), p = 0.0375; p < 0.05. The prevalence of subclinical hyperthyroidism with low serum TSH and normal serum level of fT3 was higher in the IG-10 patients (16.7%) compared with 3 (10.0%) of the CG, but the difference was not statistically significant p = 0.3970. Acute exacerbation frequency of IG was significantly higher than in the CG (1.6 ± 0.42 and 0.82 ± 0.79 respectively; p < 0.0001). A positive significant relationship between acute exacerbation frequency and TSH values was found (p < 0.0001; r = 0.82). The mean values of fT3 in the IG were significantly increasing with the increased severity of COPD. The degree of airflow limitation in COPD (FEV 1 as a percentage of the predicted value, FEV 1 %pred) was significantly negatively correlated to fT3, Pearson correlation, (R =-0.525; p = 0.000; p < 0.01). FEV 1 %pred was positively correlated with TSH (R = 0.358; p = 0.005; p < 0.01). Significant negative correlations were present between fT3 levels and both PaO 2 and SO 2 in the IG, and elevation of fT3 was associated with higher PaCO2. Conclusion: The present study confirms that both clinical and subclinical hyperthyroidism was higher in patients with COPD compared to the non-COPD group. TSH and fT3 are related to lung function. A better understanding of the correlation between thyroid gland disorders and COPD may contribute to better care of patients.
Keywords: COPD; comorbidity; thyroid gland; thyroid hormone; hyperthyroidism